STUDI KOMPARATIF ANTARA PENGGUNAAN QR QRIS DAN KOTAK INFAQ DALAM BERINFAQ DI MASJID DAARUSSALAAM GRIYA TUGU ASRI, KECAMATAN CIMANGGIS, KOTA DEPOK, JAWA BARAT - Aditya Wiranda (Jurnal Indragiri Penelitian Multidisiplin, 2022)
The Services and collection of infaq funds at the Daarussalam Griya Tugu Asri Mosque already use online and offline systems. By using the training method for the DKM administrators of the Daarussalaam Griya Tugu Asri Mosque, so that congregations and the public can make donations using the Quick Response (QR) scan menu in the application. Users only scan the QR code belonging to DKM Daarussalaam Mosque. The web-based developed application provides an infaq feature for those who will donate to the mosque without having to put money into the mosque's infaq box. This application facilitates electronic payments by integrating the Quik Response Code Indonesian Standard (QRIS) in the electronic transaction process. QRIS can also be scanned directly from web pages without the need to print. So that there will be no more loss of infaq boxes, and avoid fraud in the name of the mosque. Infaq fundraising program with a QR code system through a non-cash payment and distribution system, for transparency. With this QRIS, people who want to donate to the mosque can simply scan the QRIS with their own application without having to switch to another application. The object of this research is a comparative study between the use of QRIS and infaq boxes, while the research subject is the mosque's prosperity council or the general treasurer of the mosque who play an important role in the implementation of the Indonesian Quick Response Code payment system and infaq boxes.. The method used in  data collection is the method of interviews and methods of documentation.